Financial Distress: Studi pada Jumlah Dewan Komisaris, Karakteristik CEO, dan Leverage Perusahaan Manufaktur di Indonesia - Nikke Yusnita Mahardini; Dien Sefty Framita (The Graduate School of Sahid University, 2022)
This study aims to determine the impact of the board size of commissioners, CEO characteristics and leverage in the potential of financial distress in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This research is done using quantitative methods. The research population of 192 companies and was taken samples by 72 companies using purposive sampling. The analysis technique used is panel data regression analysis. Based on the result of the research can be concluded that the measure of the board size of commissioners, gender CEO and leverage has a significant effect on the potential of financial distress. Whereas, CEO education does not have a significant effect on the potential of financial distress.